Development of eosinophilic granulomatosis with poliangiitis (Churg-Strauss syndrome) and brain tumor in a patient after more than 7 years of omalizumab use: A case report. (March 2015) - Borekci, S; Aydin, O; Hatemi, G; Gemicioglu, B
Omalizumab is a monoclonal anti-immunoglobulin E antibody used for the treatment of severe perennial allergic asthma. Previous reports have suggested that omalizumab treatment can be associated with the development of eosinophilic granulomatosis with poliangiitis (EGPA) (formerly known as Churg-Strauss syndrome) and an increased risk of malignancy. Long-term risks of omalizumab treatment are not very well defined. Here, we report the case of a 75-year-old woman with concurrent occurrence of EGPA and brain tumor after more than 7 years of omalizumab treatment. The possibility of EGPA should be borne in mind during long-term treatment with omalizumab. Despite the absence of definitive data, an association may also exist between the development of malignancy and omalizumab use.